(3eNJUQ JGQjN OeTb dGHf YSGcQs - (3eMeO Hf ecQe Hf Ydj, CHh GdaVd, LeGd GdOjf GHf efXhQ GdCfUGQj GdQhjaYj GdEaQjbj, J (B711 (3g` s; (3GHf YSGcQ , KbI GdOjf CHh GdbGSe Ydj Hf GdMSf Hf gHI Gddg GdTGaYj GdOeTbj, GHf YSGcQ,J (B571 (3g` s
(3ChdgG (B:s
(3jHJOF HHbjI MOjK eYGhjI GHf CHj SajGf s
(3BNQgG (B:s
(3hjfJgi Edi JQLeI ehSi Hf YeQGf GdfHi Ydjg GdSdGe s
(3fSNI KGdKIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs